Pengaruh Konsumsi Rumah Tangga, Infrastruktur Listrik dan Pengeluaran Pemerintah di Kabupaten Bojonegoro - Indayah, Yulzaidah Wulan; Asmara, Kiky (Universitas Hamzanwadi, 2024)
The purpose of this research is to evaluate Bojonegoro Regency regarding whether there is a relationship between household consumption, electricity infrastructure and government spending on economic growth. The sample used in this research is the entire population of Bojonegoro Regency from which representative conclusions can be drawn for this population. The analysis method used is secondary data with time series data or time series data obtained from BPS (Central Statistics Agency) Bojonegoro Regency data with Multiple Linear Regression as the analysis method. The results obtained by this research are: 1) household consumption is known to have a negative but significant impact on economic growth due to a lack of efficiency, 2) Electrical infrastructure is known to have a negative but significant impact on economic growth due to the lack of contribution to the industrial sector , 3) government spending is known to have no influence and is also insignificant for economic growth due to the allocation of spending not being on target which causes economic growth to be hampered.